Hubungan Obesitas, Status Paritas, dan Status Gravida dengan Kejadian Anemia dalam Kehamilan di Puskesmas Rijali - Muhammad Sobri Maulana (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Anemia in pregnancy is diagnosed when Hb <11g/dL or Ht <33%. Anemia itself is caused by multifactorial, one of those are nutrition and pregnancy history. This study aims to identify the correlation between obesity, parity status and gravida status towards the number of anemia in pregnancy. This study used cross-sectional design which involved 146 pregnant women in Puskesmas Rijali. The variables such as BMI, parity status and gravida status are gathered using random sampling. The variables then are calculated using SPSS. The data is shown in the form of categorical variable after calculated using chi-square methods. This study shows no correlation between obesity and parity status with anemia in pregnancy (p>0.05). This result is supported by some others studies. In the other hand, this study shows correlation between gravida status and anemia during pregnancy (p<0.05). And the result is also supported by many others studies, one of the reason is due to malnutrition and blood loss during the previous delivery process. This study shows correlation between gravida status and anemia during pregnancy. Meanwhile, parity status and obesity doesn’t show any significant correlation.